Integrated clinical orthodontics - Davidovitch, Zeev.; Krishnan, Vinod (Chichester, West Sussex : Wiley-Blackwell, 2012)
Provides an important new resource on the clinical interactions between the practice of orthodontics and other areas of clinical dentistry and medicine. Integrates the knowledge, skills, and experience of all the disciplines of dentistry and medicine, and helps orthodontists to arrive at an accurate diagnosis and a comprehensive treatment plan. Outlines and details the management of congenital orofacial deformities, sleep disorders, aesthetic smile creation and temporomandibular joint problems, as well as specific protocols for effective communication with experts in other specialties. Uses clinical case presentations in a highly visual and practical format to illustrate the rationale and application of the interactive approach to a variety of clinical scenarios--Provided by publisher.
Includes bibliographical references and index.
Keywords: Orthodontics